ROOM ARRANGEMENT CONCEPT: THE SACRED-PROFANE OF HEIRLOOM HOUSES IN HUTAGODANG VILLAGE, MANDAILING - Cut Nuraini (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2017)
AbstractTraditional societies have always retained unique experiences and understanding about their houses. The experiences and understanding tend to be subjective, yet there is a real manifestation. This study aims to explain the concept of sacred-profane on room arrangement of heirloom houses at Mandailing society. This rationalistic study has been conducted in a descriptive-explorative way of using sacred-profane theory. The result shows that the room arrangement on heirloom houses of Mandailing society retain one space that is persistently existed, although the house is continued to grow, i.e., “Pantar Tonga” (middle room as living room). The room has become a universal pillar or axis mundi as well as sacred object. The sacred value of pantar tonga has reinforced the existence of the heirloom house until now without any significant change. Keywords: Heirloom House, Sacred-Profane, Axis-Mundi, Pantar Tonga